Computer analysis of cross sectional echocardiogram for quantitative evaluation of left ventricular asynergy in myocardial infarction. Issue 2 (February 1984) - Fujii, J; Sawada, H; Aizawa, T; Kato, K; Onoe, M; Kuno, Y
Abstract : Left ventricular asynergy in myocardial infarction was assessed quantitatively by computer analysis of the cross sectional echocardiogram. Short axis cross sectional images of the left ventricle at the levels of the mitral valve, papillary muscle, and apex were recorded by a phased array sector scanner in 30 patients with healed myocardial infarction and 15 normal controls. Endocardial and epicardial short axis images of the left ventricle were transferred from video tape to a minicomputer through the interface circuits, then digitised and processed automatically by a minicomputer. Automatic edge detection of the endocardial and epicardial wall was performed by applying sequential steps including smoothing, second derivative technique, dynamic thresholding, and approximation of boundaries by a spline curve. To quantify regional wall motion, the short axis cross sectional left ventricular wall of each level was divided into eight octants with eight axes at 45 degrees angles from the initial standard axis which was constructed from the geometric centre of the end diastolic left ventricular cavity to the posterior end of the right side of the interventricular septum. Segmental hemiaxis, segmental area, segmental wall thickness, and those changes during cardiac cycle were measured and calculated in each segment automatically by a computer. Regional contractility of the left ventricle was evaluated by percentage systolic changes of the segmental hemiaxis, area, and wall thickness. These values were significantly reduced in the infarcted left ventricular wall as defined by left ventriculography and electrocardiography. Moreover, percentage hemiaxis changes obtained by quantitative left ventriculography described by Herman and colleagues correlated well with those using our analytical method of cross sectional echocardiography in the corresponding segments. The geometric centre of the left ventricular cavity determined by the computer moved slightly towards the anterior wall during systole in normal subjects, possibly reflecting the anterior swinging motion of the heart. The geometric centre of the left ventricular cavity in myocardial infarction moved towards the infarcted wall, showing that the floating reference system was inferior to the fixed reference system for the quantification of abnormal wall motion in myocardial infarction. In conclusion, a computer analysis of the short axis cross sectional echocardiogram of the left ventricle using the fixed reference system has shown its ability to evaluate left ventricular contraction abnormalities, especially systolic wall thickening, which is relatively free of arbitrary interpretation of the wall motion caused by the anterior swinging motion of the heart.